Residential Schools Locations Project
This dataverse contains datasets associated with the Residential Schools Locations Project. This datasets in this project show the precise locations of the Residential Schools (Boarding Schools, Industrial Schools and Hostels) in Nova Scotia, Quebec, Ontario, Manitoba, Saskatchewan, Alberta, British Columbia, Yukon Territory, Northwest Territories and Nunavut. Data was created by Rosa Orlandini with significant contributions from the National Centre for Truth and Reconciliation, and minor contributions from Morgan Hite and Stephanie Pyne.
Keywords: _open access

Historical Atlas of Canada Online Learning Project
Data for maps from the Historical Atlas of Canada Online Learning Project (HACOLP), preserved here largely for preservation purposes. HACOLP was a series of interactive online maps based on maps in the published Historical Atlas of Canada series. Data deposited by Byron Modolfsky, cartographer for the Historical Atlas of Canada, summer 2019.
Keywords: _open access

The Canadian Peoples 1871-1921 census data
The Canadian Peoples (TCP) data infrastructure encompasses 40 million coded and georeferenced census records from 1852-1921 including personal, family and household characteristics for every individual in each enumeration. The Canadian Foundation for Innovation, provincial research funds in Quebec, Ontario and Alberta, nine Canadian universities and Ancestry.com have funded the project. The owner of these data, Ancestry.com, has agreed to license their use for academic research and educational purposes only, with no right to publish, transfer, share, sub-license or distribute any portion of the data. Access to data for research and educational purposes may occur upon approval of a completed application by the TCP approvals committee. Any research institution or research seeking access to any of the data within this collection will need to complete the application form and send it to the TCP project director Kris Inwood at: kinwood@uoguelph.ca The first census year for distribution is 1871; the data for other years will follow as soon as they can be made ready.
Keywords: _open access

Ingenium (Musée des sciences de l’innovation du Canada)
Ingenium – Le Musée des sciences de l’innovation du Canada à Ottawa crée des expositions hors concours, des programmes accessibles et adaptés aux familles ainsi que des recherches collaboratives qui prennent vie grâce à notre collection nationale d’artefacts.
Keywords: _open access

The Montreal daily star 1877-1951 (Graham & Co, proprietors)
Keywords: _BLRCS; _imprimé

The Montreal gazette = Gazete de Montréal (1785-1824)
Keywords: _BAnQ; _no subscription

The New Montreal gazette 1834 - Canadianaorg (Printed and Published by Robert Weir, Junior, 1834)
Keywords: _open access

Montreal Gazette 1817;1822;1823 (James Brown, 1824)
Keywords: _BLRCS; _imprimé

The Montreal gazette = Gazette de Montréal 1785-1816 ([s.n.], 1816)
Keywords: _BLRCS; _imprimé

Montreal Gazette 1824-1867 (Printed and published by T.A. Turner, 1867)
à la BLRCS Vol. 1, no. 84 [i.e. 83] (Nov. 20, 1824)-v. 93, no. 130 (June 1, 1867).
Keywords: _BAnQ; _BLRCS; _imprimé

Publications – Centre d'histoire et d'archives du travail
Keywords: _imprimé; _microfilm

Archives Deschâtelets-NDC (2023)
Les Archives Deschâtelets-NDC sont les archives historiques et administratives des missionnaires Oblats. Elles ont pour mission d’acquérir, traiter, conserver, améliorer l’accessibilité et diffuser…
Keywords: _imprimé

Revue canadienne (Canadiana)
1864-1920
Keywords: _open access

The Canadian magazine (Canadiana)
1893-1921
Keywords: _open access

Canada Census Search - Library and Archives Canada
Application Description
Keywords: _open access

The Black Press
Keywords: _open access

Artefacts Canada - Gouvernement du Canada, Ministère du Patrimoine canadien
Artefacts Canada propose un accès à de l'information sur des millions d'objets de musées, fournis par des musées et des organismes patrimoniaux de partout au Canada.
Keywords: _open access